How venture capital funding changes an entrepreneur's digital identity: more self-confidence and professionalism but less authenticity! - Jörn H. Block; Walter Diegel; Christian Fisch (Review of Managerial Science, 2023)
An entrepreneur's digital identity matters for resource acquisition and venture development. However, we know little about the factors that influence or change entrepreneurs' digital identities. This study explores how entrepreneurs' digital identities change after a venture capital (VC) funding round. Applying a language-based text analysis to a large sample of tweets from 2,094 US entrepreneurs, we analyze entrepreneurs' digital identities before and after VC funding. The results of our analysis show that VC funding can impact the entrepreneur's digital identity in both a positive and a negative way. On the positive side, entrepreneurs increasingly use language indicative of higher self-confidence, positive emotions, and increased professionalism. On the negative side, we find that the entrepreneur's digital identity loses its authenticity, particularly with high funding amounts raised. The latter can be problematic as authenticity is shown to be a critical resource that entrepreneurs possess to build legitimacy and engage stakeholders in their venture. Our study contributes to research on the consequences of VC funding for entrepreneurs as well as to research on entrepreneurial digital identities. Practical implications exist for entrepreneurs managing their entrepreneurial identities over the course of venture development.
Keywords: 650; Digital identity; Authenticity; Venture capital; Twitter; Entrepreneur; Text analysis; LIWC; Digital footprints